Cyberbullying and Empathy in the Age of Hyperconnection: An Interdisciplinary Approach - Auriemma, Vincenzo; Iorio, Gennaro; Roberti, Geraldina; Morese, Rosalba (Frontiers in Sociology, 2020)
Considering cyberbullying as a challenging frontier of analysis in the social sciences, we find ourselves today with the duty to analyze it within a much broader social context. Indeed, we must take into account the logic of exclusion, as a fact. Today, in the logic of how the Internet works, a thin line separates the victim from the perpetrator; this is also due to the Internet we know today, made up of a mass and a headless power. Trying to amplify this dichotomy, we can say that today we live in the era of the so-called “ban-opticon” (or the logic of prohibition). This logic ranges from simply removing Facebook friends from the list, to excluding sources of knowledge. This article has focused on the discussion of cyberbullying by applying an interdisciplinary approach from sociology to psychology, with the analysis of important aspects such as empathy, hyperconnection, individualization. The concept of empathy, studied several times through the terms Verstehen and Einfuhlung, has today been explored by many parties. In fact, the term Empathy has been used to describe sympathy or compassion. The interdisciplinary approach allows a broader and more innovative analysis to better understand the phenomenon of cyberbullying and to conceptualize new intervention strategies in the social and educational fields to open new frontiers in research.